How to assess ecodistrict resilience to urban heat stress under future heatwaves? A case study for the city of Paris. Issue 1 (2020) - Machard, Anaïs; Martinez, Simon; Bozonnet, Emmanuel; Lacedra, Eleonora; Inard, Christian
No abstract available